1998
DOI: 10.1677/joe.0.1570063
|View full text |Cite
|
Sign up to set email alerts
|

beta-Naphthoflavone abolishes interrenal sensitivity to ACTH stimulation in rainbow trout

Abstract: We report for the first time that -naphthoflavone (BNF) abolishes ACTH stimulation of cortisol production in rainbow trout (Oncorhynchus mykiss). There was significantly higher hepatic cytochrome P450 content and ethoxyresorufin O-de-ethylase and uridine-5 -diphosphoglucuronic acid transferase activities in BNFtreated fish than in sham-treated controls. BNF did not significantly effect either plasma turnover or tissue distribution of [ 3 H]cortisol-derived radioactivity. Hepatic membrane fluidity and hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In this study, plasma lactate returned to control levels within 4 h of acute handling, whereas plasma cortisol and glucose returned to control levels 8 h after exposure. In both cases, the time periods were similar to those observed in other studies in salmonid fish (Fast et al, 2008;Pickering et al, 1982;Wilson et al, 1998). It is noteworthy that plasma glucose levels increased in two phases.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, plasma lactate returned to control levels within 4 h of acute handling, whereas plasma cortisol and glucose returned to control levels 8 h after exposure. In both cases, the time periods were similar to those observed in other studies in salmonid fish (Fast et al, 2008;Pickering et al, 1982;Wilson et al, 1998). It is noteworthy that plasma glucose levels increased in two phases.…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with the study of Biron and Benfey (Biron and Benfey, 1994), we demonstrate here that the typical increase of plasma cortisol, glucose and lactate in response to a handling challenge takes place rapidly in rainbow trout, with all three parameters showing an increase within the initial 2 min of handling. In the available studies, these factors usually returned to control levels in a few hours, although recovery times strongly depend on species, the kind of stressor and exposure time (Aluru and Vijayan, 2006;Arends et al, 1999;Biron and Benfey, 1994;Fast et al, 2008;Pickering et al, 1982;Small, 2004;Wilson et al, 1998). In this study, plasma lactate returned to control levels within 4 h of acute handling, whereas plasma cortisol and glucose returned to control levels 8 h after exposure.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In fact, some inconsistencies have been reported in the results of several experimental studies, much of them associated with undefined and uncontrolled variables, which may alter the secretion of cortisol and glucose into the bloodstream. Most of these factors are not considered as direct stressors but have an effect on the intensity of the response which makes them a source of error (Kawauchi et al 1984;Davis and Parker 1990;Vijayan and Leatherland 1990;Lamers et al 1991;Sun et al 1992;Sun et al 1995;Reid et al 1998;Wilson et al 1998;Arends et al 1999;Fevolden et al 1999;Mommsen et al 1999;Pottinger et al 1999 Mass mortality of fish was observed following a sudden cold shock (15 °C decreases in water temperature from 27 °C to 12 °C over 24 h) in matrinxã (Brycon cephalus). In addition, a sudden 12 °C decrease in water temperature (from 27 °C to 15 °C over 24 h) caused 20% mortality in this fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Using a protocol modified from Vijayan and Leatherland [44] and Wilson et al [48], the entire kidney (containing the interrenal cells as well as other cell types such as chromaffin and renal cells) was excised and cut into $1 mm 3 pieces. The entire kidney was then transferred to one of the wells in a 24-well sterile culture plate (Corning Inc.) with 1 mL of fresh L-15, covered with tinfoil, and placed on an orbital plate rotator (Lab-Line) set at approximately 125 RPM.…”
Section: Isolated Kidney Preparationmentioning
confidence: 99%